USE OF STEM CELLS IN ACUTE PANCREATITIS - Hasanova, S.Yu. (World of Medicine and Biology, 2024)
Acute pancreatitis carries a significant disease burden with no definite treatment. They are associated with local and systemic inflammation and lead to numerous complications. Stem cell therapy has been explored for treating other diseases and has gained momentum due to its implications for acute and chronic pancreatitis. Stem cell therapy not only has the potential to aid regeneration but can also prevent pancreatic injury to other organs along with the resultant complications. Stem cells appear to have immunomodulatory properties and clinical potential, as evidenced by numerous studies conducted on animal models. A literature search on the treatment of acute pancreatitis with stem cells was performed in various sections of the Internet. A search was conducted on the Web of Science, Elsevier Science Inc., Scopus, Cochrane Central Register of Controlled Trials, Medline, Pubmed, Google Scholar, etc. by keywords: acute pancreatitis, MSCs, stromal cells, pathogenesis, endogenous intoxication, hemostasis, lipoperoxidation. A theoretical analysis of the data from the reviewed articles was carried out. This review discusses commonly used stem cells and their respective properties that show promise for treating pancreatitis. The use of stem cells in medicine is at a preclinical level. Many experiments are carried out on animals, mainly rats. However, stem cells can not only accelerate the restoration of the organ but also degenerate into tumor neoplasms. Therefore, further study of their behavior is necessary, including in treating pancreatitis, a common disease that leads to a significant deterioration or blocking of the breakdown of nutrients in the small intestine and the endocrine function of the pancreas. The article provides a detailed analysis of the results of using stem cells to treat pancreatitis. The analysis of the main trends in the treatment of pancreatitis with stem cells is carried out and the immediate prospects for the introduction of new technologies in the field of clinical research are identified.
Keywords: acute pancreatitis; stromal cells; pathogenesis; endogenous intoxication; hemostasis; lipoperoxidation